"It Just Depends on the Environment": Patterns and Decisions of Substance Use and Co-use by Adolescents. Issue 3 (4th May 2019) - Price Wolf, Jennifer; Lipperman-Kreda, Sharon; Bersamin, Melina
Abstract: This study used rich qualitative data to examine the role that social and physical contexts play in decision making related to simultaneous use of alcohol and marijuana among adolescents. In-depth, semi-structured interviews were conducted with 13 adolescents who used alcohol and marijuana within several hours of each other. Decisions about whether to use alcohol and marijuana simultaneously as well as use patterns (e.g., the sequence in which substances were used) were informed by the context and the desired effect of the substance(s). Also, simultaneous alcohol and marijuana use was described as occurring in multiple contexts, both destination and transitional. Interventions designed to reduce simultaneous alcohol and marijuana use could benefit from paying attention to substance use contexts.